2007
DOI: 10.1111/j.1439-0531.2006.00732.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative IFN‐τ Secretion after Hatching by Bovine Blastocysts Derived Ex Vivo and Completely Produced In Vitro

Abstract: The interferon-tau (IFN-tau) secretion levels after hatching by bovine blastocysts derived from in vitro maturated oocytes (Group A) and from in vivo (Group B) were investigated considering embryo quality. Only very homogeneous blastocysts of excellent or good quality were considered from day 7 of culture (Group A) and day 7 after artificial insemination with frozen-thawed from the same bull used for in vitro fertilization (Group B). All embryos were individually cultured into a 50 microl droplet of synthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…IFNT is a biomarker of embryo viability (Hernandez-Ledezma et al, 1992;Stojkovic et al, 1999;Neira et al, 2007). Production of IFNT is related to changes in glucose metabolism and the silencing of one of the two active -chromosomes (De La Fuente et al, 1999;Bermejo-Alvarez et al, 2011b).…”
Section: Discussionmentioning
confidence: 99%
“…IFNT is a biomarker of embryo viability (Hernandez-Ledezma et al, 1992;Stojkovic et al, 1999;Neira et al, 2007). Production of IFNT is related to changes in glucose metabolism and the silencing of one of the two active -chromosomes (De La Fuente et al, 1999;Bermejo-Alvarez et al, 2011b).…”
Section: Discussionmentioning
confidence: 99%
“…In cattle, IFNT mRNA and IFNT protein is first detected as the trophectoderm forms at the late morula to early blastocyst stage of development (Farin et al 1989, Farin et al 1990, Hernandez-Ledezma et al 1992), but both mRNA and protein levels are very low in blastocysts (Kubisch et al 1998, Kubisch et al 2001). In vivo or in vitro derived hatched day 7 bovine blastocysts produce very low amounts of IFNT (∼100 to 1000 pmol per day) as measured by antiviral cell protection assay (Kubisch et al 1998, Neira et al 2007). Both IFNT mRNA levels in the conceptus and detectable IFNT bioactivity, determined by antiviral assay, in the uterine flush increases substantially after day 14 of pregnancy in cattle as the conceptus grows and elongates (Short et al 1991, Ealy et al 2001, Robinson et al 2006, Groebner et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, some researches also reported that the embryos completely produced in vitro secreted more IFN‐τ than the embryos produced in vivo (Wrenzycki et al. 1999; Neira et al. 2007).…”
Section: Discussionmentioning
confidence: 99%